2006
DOI: 10.1002/pip.681
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rough reflecting substrates incorporated into thin‐film silicon solar cells

Abstract: Four different categories of rough reflecting substrates as well as a single periodic grating are incorporated and tested within n‐i‐p type amorphous silicon (a‐Si:H) solar cells. Each category is characterised by its own texture shape; dimensions were varied within the categories. Compared to flat reflecting substrates, gains in short‐circuit current density (Jsc) up to 20% have been obtained on rough reflecting plastic substrates. As long as (1) the characteristic dimensions of the textures are lower than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A direct relation exists between the microscopic features of a texture such as roughness and its light scattering performance and resulting increase in photocurrent of a deposited PV cell [31]. The topography of the texturized samples was examined by scanning electron microscopy (SEM).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…A direct relation exists between the microscopic features of a texture such as roughness and its light scattering performance and resulting increase in photocurrent of a deposited PV cell [31]. The topography of the texturized samples was examined by scanning electron microscopy (SEM).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The light trapping properties in a-Si:H nip solar cells on a variety of substrate structures have previously been reported by Daudrix et al 38 Using textured LP-CVD ZnO front contacts, the authors reported current enhancements up to 16% with respect to cells on flat substrates. Summarising our results on light trapping in a-Si:H Section 'LP-CVD ZnO and ITO Front Contacts for Thin Absorber (a-Si:H)', we find current enhancements between 8 and 18%, depending on the combination of back contact texture and the choice of front contact.…”
Section: Light Trapping and Device Performancesmentioning
confidence: 72%
“…Efficient thin film solar cells based on photoabsorbers like amorphous silicon (a-Si:H) require effective light trapping over the entire visible spectrum, especially in the region of red light [4,5]. The absorption curve for a-Si:H material gradually falls in the red spectrum region (Fig.…”
Section: Introductionmentioning
confidence: 99%